Preparation method and application of ternary ldh material

CN122999205APending Publication Date: 2026-10-30BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610929444.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,实际废水成分复杂,背景基质干扰导致该过程需要消耗大量的氧化剂,不仅增加了碳排放,还可能产生有毒中间产物引发二次污染

Benefits of technology

[0015]本发明的第四方面提供了一种酚类污染物催化降解的方法,包括如下步骤:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999205A_ABST
    Figure CN122999205A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a ternary LDH material and application thereof. The preparation method comprises the following steps: dissolving soluble nickel salt, zinc salt and cobalt salt in water to form a mixed cation solution, mixing the mixed cation solution with an alkali liquor containing hydroxyl ions and carbonate ions to perform a co-precipitation reaction, and then performing crystallization, separation and drying to obtain a NiZnCo-LDH material. The prepared NiZnCo-LDH can be used as a Fenton-like catalyst to catalyze the degradation of phenolic pollutants in water by persulfate. The catalyst generates high-valence metal oxygen species to realize the polymerization removal or mineralization of the phenolic pollutants, and the carbon resources in the pollutants are recycled into high-value-added products while the pollutants are efficiently removed, so that the catalyst has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental pollution control and advanced oxidation technology, specifically relating to a method for preparing a ternary NiZnCo-LDH material and its application in the catalytic degradation of phenolic pollutants. Background Technology

[0002] Phenolic compounds, as important chemical raw materials, are widely used in resin production, pharmaceutical dye synthesis, pesticide production, and many other fields. The large-scale use of phenolic compounds generates highly toxic phenolic wastewater, posing a threat to the ecological environment and human health. Therefore, phenolic substances are listed as environmental pollutants by many environmental organizations and are under strict monitoring; their treatment has become a major problem that urgently needs to be solved. Because phenolic pollutants have a stable benzene ring structure, they are very difficult to degrade. Common wastewater treatment methods such as flocculation, extraction, and adsorption cannot completely degrade phenol. Advanced oxidation technologies are one of the most effective technologies for treating phenolic wastewater. By adding oxidants to generate active oxides, phenolic pollutants are non-selectively mineralized into carbon dioxide and water, meeting the environmentally friendly requirements of green chemistry. Based on the different modes and types of free radical generation, advanced oxidation technologies can be divided into persulfate oxidation, ozone oxidation, photocatalytic oxidation, ultrasonic chemical oxidation, electrochemical oxidation, wet oxidation, and Fenton oxidation, among others. Persulfate advanced oxidation technology (PAO) utilizes persulfate as an oxidant to generate strong oxidizing free radicals, such as sulfate and hydroxyl radicals, under specific conditions to oxidize and degrade organic pollutants. It plays a significant role in water disinfection, soil remediation, wastewater and landfill leachate treatment, and pollutant removal. Activation methods include light, heat, and transition metals. Among various methods, transition metal activation is widely used due to its effectiveness and controllability. However, the complex composition of actual wastewater and background matrix interference mean that this process requires a large amount of oxidant, increasing carbon emissions and potentially generating toxic intermediate products that cause secondary pollution. With the global goal of "carbon peaking and carbon neutrality," environmental governance technologies urgently need to shift from "energy-consuming pollution elimination" to "resource-based recycling."

[0003] LDHs (Layered Bimetallic Hydroxides) materials possess characteristics such as stable layered structure, flexible and tunable metal composition, and abundant reaction sites, which give them significant advantages in Fenton-like reactions that activate PMS. Summary of the Invention

[0004] This invention aims to at least partially address one of the technical problems in related technologies. This invention develops a NiZnCo-LDH material for closed-loop recovery of pollutants, which can serve as a catalyst for the degradation of phenolic pollutants, utilizing the interlayer CO3²⁻ of the LDH layer. - / HCO3 -Buffering capacity and Zn sites for OH - The coordination stability of the catalyst maintains a near-neutral microenvironment during degradation. This microenvironment significantly inhibits the dissolution of active metals such as Ni and Co, improving catalyst stability and recyclability. Furthermore, by optimizing the electronic structure of Ni and Co sites through ligand field modulation, it enhances the adsorption capacity for peroxymonosulfate (PMS) and promotes the formation of high-valence metal-oxygen species. These high-valence metal-oxygen species can selectively initiate the radical polymerization of phenolic monomers via proton-coupled electron transfer (PCET) mechanisms, achieving a unified process of pollutant removal and carbon resource recovery. The aim of this study is to efficiently remove pollutants while avoiding over-mineralization and recovering carbon resources from pollutants into high-value-added products.

[0005] Specifically, the present invention provides the following technical solution: A first aspect of this application provides a method for preparing a ternary NiZnCo-LDH material, comprising: S1 dissolves soluble nickel salt, soluble zinc salt, and soluble cobalt salt together in water to obtain a mixed cation solution; S2 involves mixing a mixed cation solution with an alkaline solution containing hydroxide and carbonate ions, and then co-precipitating the mixture. After crystallization, separation, and drying, a ternary NiZnCo-LDH material is obtained.

[0006] The prepared NiZnCo-LDH material can be used as a Fenton-like catalyst for the catalytic degradation of phenolic pollutants in water by persulfate. This catalyst utilizes the amphoteric properties of Zn(OH)2 to maintain a neutral pH microenvironment, effectively inhibiting the dissolution of metal ions and improving catalyst stability and recyclability. Simultaneously, by generating high-valence metal oxygen species, it achieves the polymerization removal or mineralization of phenols, realizing the unification of pollutant removal and carbon resource recovery, demonstrating promising application prospects.

[0007] According to embodiments of the present invention, the soluble nickel salt includes at least one of nickel nitrate, nickel sulfate, or nickel chloride; The soluble zinc salt includes at least one of zinc nitrate, zinc sulfate, or zinc chloride; The soluble cobalt salt includes at least one of cobalt nitrate, cobalt sulfate, or cobalt chloride.

[0008] In the mixed cation solution, the total molar amount of soluble nickel salt, soluble zinc salt and cobalt salt is 3 to 3.5 mmol, wherein the molar ratio of soluble nickel salt, soluble zinc salt and soluble cobalt salt is 1:1:(0.3 to 0.01).

[0009] According to an embodiment of the present invention, the hydroxide alkali solution is selected from at least one of sodium hydroxide, potassium hydroxide, and ammonia water; the carbonate alkali solution is selected from at least one of sodium carbonate, sodium bicarbonate, and ammonium carbonate.

[0010] According to an embodiment of the present invention, the temperature of the coprecipitation reaction is 45~75°C, and the pH of the coprecipitation reaction is 9.5~11.5.

[0011] According to an embodiment of the present invention, the crystallization is carried out by static aging for a duration of 12 h to 24 h.

[0012] According to an embodiment of the present invention, the drying conditions are drying at 60~80°C for 6 h~12 h.

[0013] A second aspect of the present invention provides a ternary NiZnCo-LDH material obtained by the preparation method of the first aspect described above.

[0014] A third aspect of the present invention provides the application of the above-described ternary NiZnCo-LDH material in the catalytic degradation of phenolic pollutants. The phenolic pollutants mentioned include at least one of phenol, chlorophenol, alkylphenol, or bisphenol A.

[0015] A fourth aspect of the present invention provides a method for the catalytic degradation of phenolic pollutants, comprising the following steps: The NiZnCo-LDH material described in the second aspect above is added to water containing phenolic pollutants, and persulfate is added to carry out a Fenton-like degradation reaction; wherein the phenolic pollutants include at least phenol.

[0016] According to embodiments of the present invention, the concentration of phenol is 10–50 mg / L, the concentration of persulfate is 0.05–2 mmol / L, the concentration of NiZnCo-LDH material is 0.05–2 g / L, and the degradation reaction time is 30–60 min. These conditions enable efficient degradation, meeting the needs of rapid wastewater treatment in practice, thereby achieving efficient and stable removal of phenolic pollutants from water.

[0017] Compared with the prior art, the beneficial effects of this application are at least as follows: (1) The preparation method provided by this invention achieves uniform mixing of Ni, Zn, and Co at the molecular level by co-dissolving three soluble metal salts, ensuring the formation of a single LDH crystalline phase during co-precipitation. This lays a solid structural foundation for the electronic structure regulation and synergistic catalysis among the three metal sites. By precisely introducing carbonate ions into the alkaline solution, the LDH is utilized to react with CO32-. 2- Its strong affinity anchors it in the interlayer domain, directly constructing the CO3²⁺ that is indispensable in subsequent reactions. - / HCO3- The buffer system avoids complex post-processing anion exchange steps. This coprecipitation route involves only ambient temperature and pressure operation, requiring no organic template agents or high-temperature and high-pressure equipment. It offers a wide process window with good repeatability, facilitating large-scale production. The introduction of the crystallization step effectively promotes the ordered arrangement and growth of metal hydroxide lamellars, significantly reduces crystal structure defects, and further enhances the chemical stability and active site uniformity of the material in aqueous reactions.

[0018] (2) This invention utilizes NiZnCo-LDH material as a catalyst to selectively generate high-valence metal oxygen species in a Fenton-like reaction, and efficiently initiates the polymerization of phenolic pollutants through a proton-coupled electron transfer mechanism, avoiding the carbon emissions and toxic intermediate products caused by excessive mineralization in traditional advanced oxidation technologies, and achieving the unity of pollutant removal and high-value-added recovery of carbon resources.

[0019] (3) Utilizing the interlayer CO3² of LDH - / HCO3 - Buffering capacity and Zn sites for OH - The coordination stability of the catalyst allows it to spontaneously maintain a near-neutral pH microenvironment during the reaction, effectively inhibiting the dissolution of active metals such as Ni and Co, and significantly improving the stability and recyclability of the catalyst. At the same time, this buffering effect enables the catalyst to maintain high efficiency activity over a wide range of initial pH values ​​in water, overcoming the dependence of traditional Fenton catalysts on harsh pH conditions.

[0020] The NiZnCo-LDH material of this invention can be used as a catalyst to achieve efficient and stable removal of phenolic pollutants in water, providing a reference for environmental remediation. Attached Figure Description

[0021] Figure 1 These are the XRD patterns of the NiZnCo-LDH materials and NiZn-LDH materials prepared in Examples 1-4 and Comparative Example 1 of this invention.

[0022] Figure 2 This is a TEM image of the NiZnCo-LDH material prepared in Example 1 of this invention.

[0023] Figure 3 These are the ultraviolet absorption spectra of phenol degradation obtained by the materials prepared in Examples 1-4 and Comparative Example 1.

[0024] Figure 4 The graph shows the EPR test results of the NiZnCo-LDH materials prepared in Examples 1 and 4, which are active species. Detailed Implementation

[0025] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.

[0026] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased on the market or prepared by existing methods.

[0027] A first aspect of this application provides a method for preparing NiZnCo-LDH material, comprising: S1 dissolves soluble nickel salt, soluble zinc salt, and soluble cobalt salt together in water to obtain a mixed cation solution. S2 mixes the mixed cation solution with an alkaline solution and performs a co-precipitation reaction, followed by crystallization, separation, and drying to obtain NiZnCo-LDH.

[0028] According to a specific embodiment, the nickel salt includes at least one of nickel nitrate, nickel sulfate, or nickel chloride; the zinc salt includes at least one of zinc nitrate, zinc sulfate, or zinc chloride; and the cobalt salt includes at least one of cobalt nitrate, cobalt sulfate, or cobalt chloride.

[0029] According to a specific embodiment, the total molar amount of nickel salt, zinc salt, and cobalt salt in the mixed cation solution is 3-3.5 mmol, wherein the molar ratio of nickel salt, zinc salt, and cobalt salt is 1:1:(0.3-0.01). In this invention, the molar ratio of Ni, Zn, and Co is a core control parameter. Co is a key active component for activating persulfate (PMS), and its Co²⁻ + / Co³ + Redox pairs can effectively promote the breaking of the OO bonds in PMS, generating high-valence metal oxygen species (Co(IV)=O) or sulfate radicals. However, excessive Co doping accelerates the over-decomposition of PMS, leading to ineffective consumption of the oxidant and increasing the risk of Co dissolution. Conversely, insufficient doping results in a lack of active sites, making it difficult to effectively activate PMS. Therefore, this invention selects a wide molar ratio range of Ni:Zn:Co = 1:1:(0.3~0.01). The introduction of Ni can form a bimetallic synergistic effect with Co. + / Ni³ + Redox pairs can promote Co³ + / Co² + The cyclic regeneration of Ni helps maintain its catalytic activity, while Ni, as a framework element for LDH layers, contributes to the stability of the layered structure. Zn² +In LDH layers, Zn sites provide structural support and can adjust the bond lengths of adjacent metal-oxygen bonds, thereby affecting the electronic structure of active sites. Simultaneously, Zn sites influence the electronic structure of OH groups. - It has coordination stability and interacts with interlayer CO3² - / HCO3 - Together, they form a buffer system to maintain a near-neutral reaction microenvironment. This design allows the catalyst to maintain high activity across a wide pH range, including acidic, neutral, and alkaline conditions. More importantly, the introduction of Co alone can easily lead to a dominant free radical pathway (overmineralization), while the introduction of Zn can modulate the electronic structure of Ni and Co sites, enhancing the adsorption of PMS and the selective formation of Ni(IV)=O or Co(IV)=O species. This guides the reaction along a non-radical high-valence metal pathway, achieving selective polymerization of phenols rather than overmineralization. Furthermore, the general formula for LDH is [M²]. + 1-x M³ + x (OH)2] x+ (A n- ) x / n ·mH2O requires a specific ratio of divalent and trivalent metal ions to maintain the charge balance and structural stability of the laminate. In this invention, Ni²⁺ + and Zn² + Co³ is a divalent metal. + (or part of Co²) + The nickel, zinc, and cobalt salts are trivalent / variable valence metals, and the above molar ratio range ensures the complete formation of the LDH layered structure. The molar ratios of the nickel, zinc, and cobalt salts can be 1:1:0.3, 1:1:0.2, 1:1:0.1, 1:1:0.05, 1:1:0.03, etc. According to a preferred embodiment, the molar ratio of the nickel, zinc, and cobalt salts is 1:1:0.3.

[0030] The alkaline solution includes hydroxide ions and carbonate ions, wherein the hydroxide ions are at least one of sodium hydroxide, potassium hydroxide, and ammonia water, and the carbonate regulator is at least one of sodium carbonate, sodium bicarbonate, and ammonium carbonate.

[0031] According to a specific embodiment, the temperature of the co-precipitation reaction in S2 is 45~75℃; according to a preferred embodiment, the temperature of the co-precipitation reaction in S2 is 50~70℃. Temperature is a key parameter affecting the crystallinity and grain size of LDH. Within this temperature range, the atomic diffusion rate is moderate, which is conducive to the orderly stacking of layers and the complete development of grains. When the temperature is too low, the crystallization kinetics are slow and the crystallinity of the product is poor; when the temperature is too high, it may accelerate particle agglomeration and increase energy consumption, which is not conducive to industrial scale-up. At 45~75 °C, the hydrolysis and precipitation reaction of metal salts reach a good dynamic equilibrium, which is conducive to the formation of LDH products with uniform composition and regular structure. In the examples, 65 °C is preferred. At this temperature, the (003) interplanar spacing of LDH is 0.76 nm, the crystal form is complete, and the layered structure is clear.

[0032] The coprecipitation reaction described in S2 has a pH of 9.5 to 11.5; according to a preferred embodiment, the pH is 10 to 11. This pH range is Ni². + Zn² + Co² + / Co³ + The complete region of hydroxide precipitation is also the optimal condition for the orderly stacking of LDH layers. This invention uses a CO3²⁻-containing... - Mixed alkaline solution, CO3² - As an interlayer anion, CO3²⁻ is crucial for maintaining the layered structure of LDH. At pH 10–11, CO3²⁻… - H2CO3 is the dominant form of CO3²⁻ (pKa2 = 10.33), which favors its dominance. - Effective intercalation. When the pH is below 9.5, some metal ions do not precipitate completely, which may lead to the formation of non-LDH impurities (such as metal hydroxides alone); when the pH is above 11.5, Zn(OH)2 and Co(OH)2 may be over-dissolved to form zincates / cobaltates, which disrupts the stoichiometry of LDH.

[0033] In S2, crystallization is carried out through static aging for 12 to 24 hours; according to a preferred embodiment, the static aging time in S2 is 18 to 24 hours. During the aging process, small grains gradually transform into large grains through a dissolution-recrystallization mechanism (Ostwald ripening), reducing crystal defects and increasing crystallinity. The aging time of 12 to 24 hours is sufficient for LDH grains to grow sufficiently and tend towards perfection. Simultaneously, CO3²⁻ is generated during the aging process. - Sufficient aging time is required to allow the ions to penetrate the interlayer and establish a stable electrostatic interaction with the layers, ensuring the uniformity of LDH interlayer spacing. Insufficient aging time results in uneven distribution of anions between the layers; excessive aging time increases energy consumption and labor time, which is detrimental to industrial production.

[0034] The drying conditions are 60°C to 80°C for 6 to 12 hours; according to a preferred embodiment, the drying conditions are 70°C to 80°C for 10 to 12 hours. LDH contains a large number of water molecules between its layers, and the drying process needs to be carried out under mild conditions. 60-80°C can effectively remove interlayer water and surface adsorbed water while avoiding the collapse of the layered structure. When the temperature exceeds 80°C, some metal hydroxides may decompose and transform into metal oxides (LDO), destroying the layered structure of LDH. Therefore, mild drying conditions ensure that the product retains the complete LDH crystalline phase.

[0035] The NiZnCo-LDH material obtained by the aforementioned preparation method can be used as a catalyst for the heterogeneous Fenton-like degradation of phenol, comprising the following steps: adding the NiZnCo-LDH material to water containing phenol, mixing well, adding persulfate to carry out a Fenton-like degradation reaction, wherein the concentration of phenol is 10–50 mg / L, the amount of persulfate is 0.05–2 mmol / L, the amount of NiZnCo-LDH material is 0.05–2 g / L, and the degradation time is 30–60 min. Benefiting from the introduction of Zn and interlayer CO3²⁻… - / HCO3 - Due to its buffering effect, the catalyst maintains high activity in acidic, neutral, and alkaline waters, overcoming the stringent pH dependence of traditional Fenton catalysts (2.8-3.5). Furthermore, the catalyst maintains high catalytic performance even after multiple cycles under natural pH conditions, effectively reducing the cost of catalyst use.

[0036] The present application will be further illustrated by the following examples. It should be noted that these examples are only for the purpose of facilitating understanding by those skilled in the art and should not be construed as limiting the scope of protection of the present invention. Unless otherwise specified, the reagents used in the examples are commercially available.

[0037] Example 1 Example 1 prepared NiZnCo-LDH material according to the following method, including: (1) Weigh 1.5 mmol of Zn(NO3)2•6H2O, 1.5 mmol of Ni(NO3)2•6H2O and 0.5 mmol of Co(NO3)2•6H2O, add them to 50 ml of deionized water, mix thoroughly and let them dissolve completely to obtain solution A; (2) Take 100 ml of a mixed alkaline solution of 0.375 M Na2CO3 and 0.875 M NaOH as solution B; (3) Slowly add solution B to solution A, control the pH to about 10~11, age the resulting suspension at 65 ℃ for 24 h, wash and dry to obtain NiZnCo-LDH material.

[0038] Example 2 Example 2 prepared NiZnCo-LDH material according to the following method, including: (1) Weigh 1.5 mmol of Zn(NO3)2•6H2O, 1.5 mmol of Ni(NO3)2•6H2O and 0.3 mmol of Co(NO3)2•6H2O, add them to 50 ml of deionized water, mix thoroughly and let them dissolve completely to obtain solution A; (2) Take 100 ml of a mixed alkaline solution of 0.375 M Na2CO3 and 0.875 M NaOH as solution B; (3) Slowly add solution B to solution A, control the pH to about 10~11, age the resulting suspension at 65 ℃ for 24 h, wash and dry to obtain NiZnCo-LDH material.

[0039] Example 3 Example 3 prepared NiZnCo-LDH material according to the following method, including: (1) Weigh 1.5 mmol of Zn(NO3)2•6H2O, 1.5 mmol of Ni(NO3)2•6H2O and 0.15 mmol of Co(NO3)2•6H2O, add them to 50 ml of deionized water, mix thoroughly and let them dissolve completely to obtain solution A; (2) Take 100 ml of a mixed alkaline solution of 0.375 M Na2CO3 and 0.875 M NaOH as solution B; (3) Slowly add solution B to solution A, control the pH to about 10~11, age the resulting suspension at 65 ℃ for 24 h, wash and dry to obtain NiZnCo-LDH material.

[0040] Example 4 Example 4: NiZnCo-LDH material was prepared according to the following method, including: (1) Weigh 1.5 mmol of Zn(NO3)2•6H2O, 1.5 mmol of Ni(NO3)2•6H2O and 0.015 mmol of Co(NO3)2•6H2O, add them to 50 ml of deionized water, mix thoroughly and let them dissolve completely to obtain solution A; (2) Take 100 ml of a mixed alkaline solution of 0.375 M Na2CO3 and 0.875 M NaOH as solution B; (3) Slowly add solution B to solution A, control the pH to about 10~11, age the resulting suspension at 65 ℃ for 24 h, wash and dry to obtain NiZnCo-LDH material.

[0041] Comparative Example 1 Comparative Example 1 prepared NiZn-LDH material according to the following method, including: (1) Weigh 1.5 mmol of Zn(NO3)2•6H2O and 1.5 mmol of Ni(NO3)2•6H2O, add them to 50 ml of deionized water, mix thoroughly and let them dissolve completely to obtain solution A; (2) Take 100 mL of a mixed alkaline solution of 0.375 M Na2CO3 and 0.875 M NaOH as solution B; (3) Slowly add solution B to solution A, control the pH to about 10~11, age the resulting suspension at 65 ℃ for 24 h, wash and dry to obtain NiZn-LDH material.

[0042] The NiZnCo-LDH materials prepared in Examples 1-4 and the NiZn-LDH material prepared in Comparative Example 1 were tested using X-ray diffraction, and their XRD patterns are shown below. Figure 1 As shown. From Figure 1 It can be seen that the diffraction peaks of the (003), (012), and (110) crystal planes appear, confirming the successful preparation of NiZnCo-LDH and NiZn-LDH materials.

[0043] The NiZnCo-LDH material prepared in Example 1 was tested using transmission electron microscopy, and its TEM image is shown below. Figure 2 As shown, LDH exhibits a typical lamellar structure. Analysis of its clear lattice fringes reveals a crystal plane spacing of 0.76 nm, corresponding to the (003) crystal plane, further confirming the successful synthesis of the LDH phase.

[0044] The phenol degradation performance of the materials prepared in Examples 1-4 and Comparative Example 1 was tested using a UV-Vis spectrophotometer. 50 mL of a 10 mg / L phenol solution was measured into an Erlenmeyer flask, and 30 mg of potassium peroxymonosulfate (PMS) and 15 mg of each of the prepared materials were added. The mixture was stirred at room temperature for 30 min. 3.0 mL of sample was taken periodically, and the supernatant was filtered through a 0.22 μm membrane to further determine the composition and concentration of the solution. Sodium thiosulfate was added promptly to quench the reaction and terminate it. Subsequent UV-Vis spectrophotometric analysis showed that phenol was efficiently degraded.

[0045] The results are as follows Figure 3 As shown, the absorption peak of phenol disappeared within 30 min, indicating that NiZnCo-LDH has good degradation performance. At the same time, the polymerization product of NiZn-LDH was stably generated at 245 nm, indicating that this type of Fenton catalyst can efficiently remove pollutants while avoiding over-mineralization and recovering carbon resources in pollutants into high-value-added products, which has good application prospects.

[0046] The active species of the NiZnCo-LDH materials prepared in Examples 1 and 4 were determined using electron paramagnetic resonance spectroscopy, such as... Figure 4 As shown. Compared to Example 4, in Example 1, no significant DMPO-·OH or DMPO-SO4· precipitate was observed in the presence of the DMPO scavenger. - Instead of characteristic peaks, a typical signal of non-radical oxidation of DMPO was detected, confirming that the catalytic system is mainly dominated by the non-radical pathway.

[0047] The above results demonstrate that the ternary layered bimetallic hydroxide provided by this invention possesses excellent catalytic degradation performance for phenol. Compared to binary NiZn-LDH, NiZnCo-LDH can inhibit the formation of phenol polymerization byproducts, achieving efficient degradation of pollutants while simultaneously realizing the resource recovery of pollutant carbon resources. EPR test results prove that the amount of cobalt doping can significantly alter the catalytic pathway of NiZnCo-LDH activating potassium persulfate: the system in Example 4 with low cobalt content can produce... OH, SO4 - Free radicals, mainly through the free radical oxidation pathway; the system in Example 1 with high cobalt content hardly generates free radicals, and the catalytic process is dominated by non-free radical pathways, indicating that by controlling the amount of Co doping in the LDH metal component, the type of active species and the oxidation reaction mechanism of the catalytic system can be directionally controlled.

[0048] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a ternary NiZnCo-LDH material, characterized in that, include: A mixed cation solution is obtained by dissolving soluble nickel salt, soluble zinc salt, and soluble cobalt salt together in water. The mixed cation solution was mixed with an alkaline solution containing hydroxide and carbonate ions, and a co-precipitation reaction was carried out. After crystallization, separation, and drying, ternary NiZnCo-LDH was obtained.

2. The preparation method of the ternary NiZnCo-LDH material according to claim 1, characterized in that, The soluble nickel salt includes at least one of nickel nitrate, nickel sulfate, or nickel chloride; The soluble zinc salt includes at least one of zinc nitrate, zinc sulfate, or zinc chloride; The soluble cobalt salt includes at least one of cobalt nitrate, cobalt sulfate, or cobalt chloride.

3. The preparation method of the ternary NiZnCo-LDH material according to claim 1, characterized in that, In the mixed cation solution, the total molar amount of the soluble nickel salt, soluble zinc salt and soluble cobalt salt is 3 to 3.5 mmol, and the molar ratio of the soluble nickel salt, soluble zinc salt and soluble cobalt salt is 1:1:(0.3 to 0.01).

4. The preparation method of the ternary NiZnCo-LDH material according to claim 1, characterized in that, The hydroxide alkali solution is selected from at least one of sodium hydroxide, potassium hydroxide, and ammonia water; The carbonate alkaline solution is selected from at least one of sodium carbonate, sodium bicarbonate, and ammonium carbonate.

5. The method for preparing the ternary NiZnCo-LDH material according to claim 1, characterized in that, The temperature of the coprecipitation reaction is 45~75℃, and the pH of the coprecipitation reaction is 9.5~11.

5.

6. The method for preparing the ternary NiZnCo-LDH material according to claim 1, characterized in that, The crystallization is carried out by static aging, with an aging time of 12 h to 24 h.

7. The method for preparing the ternary NiZnCo-LDH material according to claim 1, characterized in that, The drying conditions are 60-80℃ for 6-12 hours.

8. A ternary NiZnCo-LDH material, characterized in that, The preparation method according to any one of claims 1-7 is obtained.

9. The application of the ternary NiZnCo-LDH material according to claim 8 in the catalytic degradation of phenolic pollutants.

10. A method for the catalytic degradation of phenolic pollutants, characterized in that, Includes the following steps: The ternary NiZnCo-LDH material of claim 8 is added to a water body containing phenolic pollutants, and persulfate is added to carry out a Fenton-like degradation reaction; wherein the phenolic pollutants include at least phenol; Optionally, the concentration of phenol is 10–50 mg / L, the concentration of persulfate is 0.05–2 mmol / L, the concentration of NiZnCo-LDH material is 0.05–2 g / L, and the degradation reaction time is 30–60 min.